The Rule of The Jungle in Pakistan: A Case Study on Corruption and Forest Management in Swat - Lorenzo Pellegrini (Fondazione Eni Enrico Mattei (FEEM), 2007)
Corruption in the forest sector of Swat, Pakistan is impairing the sustainable management of forest. We analyze corruption in a case study setting against the backdrop of the reform options that are most often cited as possible solutions. As we highlight in this study, the crime and punishment approach is not feasibly implemented if the overall institutional environment is weak. Since countrywide overhaul of corruption through sweeping reform programs, the other reform approach, is a difficult and lengthy task, there is a need for an alternative kind of reform. In the case of a corruption-ridden centralised forest management regime, institutional reform should move away from enforcement of existing institutions and promote communal management of natural resources by locals.
Keywords: D73; Q24; Q57; 330; Corruption; Forest Management; Environmental Policy; Institutional Reform; Korruption; Forstwirtschaft; Umweltpolitik; Pakistan